2019
DOI: 10.1126/sciadv.aau8038
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale magnetic imaging of ferritins in a single cell

Abstract: The in situ measurement of the distribution of biomolecules inside a cell is one of the important goals in life science. Among various imaging techniques, magnetic imaging (MI) based on the nitrogen-vacancy (NV) center in diamond provides a powerful tool for the biomolecular research, while the nanometer-scale MI of intracellular proteins remains a challenge. Here, we use ferritin as a demonstration to realize the MI of endogenous proteins in a single cell using the NV center as the sensor. With the scanning, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…It is widely used in room-temperature magnetic sensing and capable of measuring spins in a single-molecular level. [11][12][13][14][15][16][17][18][19][20][21][22] Reconstructing full information of the magnetic field vector (i.e., including magnitude and orientation) is often crucial in applications such as biological magnetic field sensing and the condensed matter physics. 18,[23][24][25] For single NV center, the basic idea of measuring magnetic field is to detect the frequency shift due to the Zeeman effect by the optically detected magnetic resonance (ODMR) procedure.…”
Section: Introductionmentioning
confidence: 99%
“…It is widely used in room-temperature magnetic sensing and capable of measuring spins in a single-molecular level. [11][12][13][14][15][16][17][18][19][20][21][22] Reconstructing full information of the magnetic field vector (i.e., including magnitude and orientation) is often crucial in applications such as biological magnetic field sensing and the condensed matter physics. 18,[23][24][25] For single NV center, the basic idea of measuring magnetic field is to detect the frequency shift due to the Zeeman effect by the optically detected magnetic resonance (ODMR) procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Notable accomplishments include both mapping magnetic ions and nanostructures in living cells and noninvasive detection of neuronal action potentials. 16 , 108 114 The current state-of-the-art quantum sensor in this arena, the NV center in diamond, has demonstrated sensing at the single-cell and, with complementary targeting strategies, even the single-molecule level. 14 , 16 , 113 Furthermore, these sensors have detected individual nuclear and electronic spins in individual proteins and, with recent advancements in single nuclear spin detection by NV centers, point the way toward single-molecule and single -spin magnetic resonance techniques in biological systems.…”
Section: Opportunities For Molecular Quantum Sensorsmentioning
confidence: 99%
“…A theoretical foundation for this method was first proposed some ten years ago [120], and early experimental work has shown that ferritin can be detected by individual nanodiamonds [112], as well as a bulk diamond chip [121]. It has also been combined with AFM to detect ferritin aggregates inside a cell [122].…”
Section: Ferritin-bound Iron Measurement Techniquesmentioning
confidence: 99%